As matrizes históricas da inspeção escolar no Brasil : mecanismo de controle do trabalho docente em Alagoas (1840-1889) - Pauferro, Nezilda do Nascimento Silva (2010)
The aim of this study is to investigate the matrices of inspection historical school in Brazil,especially in Alagoas, in the period 1840 to 1889.This in order to understand how organized school education in the Empire and, more specifically,as was the function of surveyor and its relationship with the teaching profession..For our theoretical and methodological support-in, authors historiographical bound for the replacement of Brazilian education, which have looked on the 19 the century, turning their eyes for both national and local level, in the case of our research ,is the Province of Alagoas. Among these authors highlight-if Gondra and Schueler (2008), which expanded our knowledge about the relations between education, power and society in Brazilian Empire; Veiga (2007), which deals with the education as a project of civilization underway in western societies from the 15th century and its consolidation in XIX and XX centuries; Bloch (2001), which made us realize the importance of this for understanding the past and that in order to understand today: Verçosa (2001),which gave us a more comprehensive reading trajectory educational alagoana; Moacyr Primitive (1939) whose studies is of fundamental importance for the history of Brazilian education, especially for those who dedicated studies on the 19th century and Costa (1931), which subsidised understanding alagoana education in the nineteenth century. After a careful reading of texts of these authors, we understand which the place of writing of the men of the Empire.In the project of the civilization of Brazilian society the school was understood as an institution that attended to this end, and the professor contribute to the moralizing and standardization of a society which, in essence, was uneven. The inspectors as government representatives were part of a strategy to ensure the continued this project to institutionalize the schooling directed to social layers of the Empire. So is defined its function.Particularly in the Province of Alagoas the inspectors, parishioner or municipal, had the role of visiting schools and accountability to Inspector General of studies. Each teacher was obliged to inform on the functioning of classes, in respect of didactic material, the frequency of student and the use of learning. We can say, therefore, the inspector school was responsible for articulate the links between teachers and inspector general of studies. We consult several documents, since manuscripts maps studies by teachers, crafts and reports of inspectors parochial and general studies, which outlined traces of pedagogy school Alagoas in Empire. These documents also enabled understand who played the role of inspectors, since presidents of the province, directors general studies, representatives of Chambers Municipal, but also people that even not having a knowledge of the letters more substantiated, formed part of a group economically or politically that favors their access to that function. We note that all had as end of the surveillance of the teaching work, which was fundamental to the homogenization of Brazilian schooling process, as well as to constitute register which tell the story of the Empire.